Factors influencing utilization of Voluntary Counseling and Testing Services among Kenya Ports Authority employees in Mombasa, Kenya - Wangui, J. K.; Kikuvi, G. M.; Msanzu, J. B. (Global Journal of Health Sciences, 2016)
Purpose: HIV and AIDS remains to be a problem of public health importance worldwide. About 36.9 million people were living with HIV and AIDS by the end of 2014. The greatest burden of the epidemic with about 25.8 million people living with HIV was in Sub-Saharan Africa which also accounted for 66% of the global total of new HIV infections. In Kenya, HIV burden stands at 1.6 million. Early access to testing and treatment would facilitate containing the pandemic and thus achieving 90-90-90 targets by 2020 and end AIDS epidemic by 2030. Voluntary Counseling and Testing (VCT) aids stigma reduction and also allows for early uptake of services such as counseling for positive living, social support, legal advice and future planning. The objective of this study was to determine factors influencing utilization of voluntary counseling and testing services among Kenya Ports Authority employees in Mombasa. Methodology: The study participants were drawn from the 32 departments using probability proportion to size sampling method (PPS);respondents within departments were randomly selected. Quantitative data was collected using semi-structured questionnaires. Data was analyzed using the Statistical Package for Social Sciences Version 16 (SPSS 16). Descriptive statistics were used to analyze quantitative data. Regression andcorrelation analysis were used to analyze the associations between dependent and independent variables. Results: The prevalence of VCT utilization among the KPA, Mombasaemployees was 91.2%. Utilization of VCT services by the employees was supported by marital status, education level and religion, among other factors. Employees were keen to know their status but the majority felt uncomfortable being tested for HIV by someone they knew. Although majority had taken the HIV test more than once, some still declined due to no apparent reason, felt it not necessary, feared positive results or thought there was no cure for AIDS. However, those who tested received feedback promptly and communicated the test results to their partners, although majority did not accompany them. Fewer females disclosed their HIV results compared to males. Regression analysis on data from 295 respondents indicated a positive relationship between the factors analyzed and VCT uptake (R2 = 0.600). Being married was significantly positively associated with VCT utilization among employees (p=0.015), so was being accompanied by a partner (p=0.017), and communication of results (p=0.034). The respondents agreed that ARVs improved immunity and made one stronger. More male than female respondents used condoms during sex and also more male than female respondents disclosed their HIV status. The study further indicated that there was a marginal relationship between VCT utilization and the aspect of being denied recruitment or promotion because of HIV status (odds ratio at 95% CI: 0.982, 2.886; p=0.057). Unique contribution to practice and policy: From the study findings, employees were keen to know their status but the majority felt uncomfortable being tested for HIV by someone they knew and thus a significant number attended VCT outside KPA. A program to help support those who attend VCT outside KPA should be implemented so that such facilities do not run short of VCT program requirements. Although majority had taken the HIV test more than once, those who declined should be encouraged to take the test in order to know their status for prevention and early treatment. Since more male than female respondents disclosed their HIV status and more male than female respondents used condoms during sex, more innovative methods should be devised to encourage female employees to disclose their status and use condom. Special attention should be given to married employees and females.